ASUHAN KEPERAWATAN PADA KLIEN DEMAM BERDARAH DENGUE (STUDI LITERATUR): ASUHAN KEPERAWATAN PADA KLIEN DEMAM BERDARAH DENGUE (STUDI LITERATUR) - Pratama, Apriawan Aji; Muniroh, Siti; Zuliani, Zuliani (LPPM STIKes Bahrul Ulum Jombang, 2021)
Dengue Hemorrhagic Fever (DHF) is an acute infection caused by orbovirus (Arthopodbron virus) and is transmitted through Aedes mosquito bites (Aedes albopictus dan Aedes aegypti). Until now, 4 types of dengue virus were introduced that can cause dengue fever and dengue fever. Regarding the occurrence of dengue fever can be stated as follows. After the dengue virus enters the human body through the bite of the Aedes mosquito the patient's body forms immunity to the disease if the patient is attacked for the second or more times the type of virus is different, it will cause an immunological reaction in the body (Ngastiyah, 2015). The methodology in writing scientific papers uses a literature study with four clients in the scientific papers of the D3 Nursing study program at the Faculty of Health, Unipdu, Jombang in 2014-2018 with the same title, namely nursing care for clients of dengue fever. The results of the implementation of nursing care in four clients with dengue hemoragic fever (DHF), obtained all four clients experience the disease (DHF) with a diagnosis of hyperthermia. Nursing actions made can be carried out well because of the support of all health workers, clients and families and hospital infrastructure but cannot be carried out in a row.